2022
DOI: 10.3389/fmed.2022.920726
|View full text |Cite
|
Sign up to set email alerts
|

A Tapered Cuff Tracheal Tube Decreases the Need for Cuff Pressure Adjustment After Surgical Retraction During Anterior Cervical Spine Surgery: A Randomized Controlled, Double-Blind Trial

Abstract: BackgroundSurgical retraction to expose the vertebrae during anterior cervical spine surgery increases tracheal tube cuff pressure and may worsen postoperative sore throat and dysphonia. This randomized double-blind study investigated the effect of cuff shape on intraoperative cuff pressure and postoperative sore throat and dysphonia.MethodsEighty patients were randomized to tracheal intubation with a tapered cuff or a conventional cylindrical high-volume low-pressure cuff (control) during anesthesia. Intraope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
(85 reference statements)
0
2
0
1
Order By: Relevance
“…In another study, it was found that ET with a conical cuff caused significantly less gastric secretion leakage compared to cylindrical cuffed tubes and was more effective in preventing the development of VAP (32,33) . In a study conducted in patients undergoing cervical surgery, it was found that the ETCP value measured in the conical cuff changed much less frequently during surgery and the cuff pressure was lower than in cylindrical cuffed endotracheal tubes (34) .…”
Section: Discussionmentioning
confidence: 95%
“…In another study, it was found that ET with a conical cuff caused significantly less gastric secretion leakage compared to cylindrical cuffed tubes and was more effective in preventing the development of VAP (32,33) . In a study conducted in patients undergoing cervical surgery, it was found that the ETCP value measured in the conical cuff changed much less frequently during surgery and the cuff pressure was lower than in cylindrical cuffed endotracheal tubes (34) .…”
Section: Discussionmentioning
confidence: 95%
“…Since a raise in cuff pressure is highly associated with postoperative airway complications, such as stridor and sore throat ( 4 , 17 , 23 ), it is appropriate to minimize changes in the patient’s neck posture. Nevertheless, movement of the head and neck is necessary to facilitate surgical access, and a typical example is otorhinolaryngologic surgery, as well as thyroid surgery and cervical spine surgery ( 24 ). Therefore, we suggest that continuous monitoring of the ETT cuff pressure should be implemented, especially in otorhinolaryngologic surgeries requiring position changes near the airway.…”
Section: Discussionmentioning
confidence: 99%
“…Neue technische Entwicklungen wie dünne Materialien für Cuffmanschetten oder die Form des Cuffs (Konus) mit dem Ziel der besseren Abdichtung konnten bisher in klinischen Studien zur Prävention der VAP nicht überzeugen [13,14]. Allerdings gibt es nun Hinweise, dass eine bessere intraoperative Abdichtung bei Manipulationen am Hals mit einem konischen Cuff gelingen kann [15].…”
Section: Take Home Messageunclassified